In-vitro effect of the methanolic extract of Morinda citrifolia against the life cycle of Dermatobia hominis - Dumar Alexander Jaramillo Hernández; Rafael Felipe Quevedo Carrillo; Diego Arnaldo Cadena Franco; Angélica Elizabeth Gonzalez Reina; Lida Carolina Lesmes-Rodríguez; Luz Natalia Pedraza-Castillo (Vitae)
Background: bovine cutaneous dermatobiosis or furuncular myiasis caused by Dermatobia hominis is a parasitosis that mainly affects bovines in the tropics and represents a particular interest in public health as zoonosis. Its control is based on ivermectins, which have long withdrawal times, affecting the productive dynamics within dairy cattle herds. Objective: to assess the in-vitro effect of the methanolic extract of the M. citrifolia ripe fruit against the life cycle of D. hominis. Methods: D. hominis larvae were taken directly from naturally parasitized bovine skins. These larvae were exposed by immersion to different concentrations of the methanolic extract of M. citrifolia (10, 50, 100, 200, 300, 400, 460 mg/mL) diluted in distilled water. Ivermectin 1% was used as a positive control, and distilled water as a negative control. Subsequently, the larvicidal activity was evaluated in the first 48 hours post-immersion (PI), the pupicidal activity within 10 to 23 days PI, and the inhibition of the imagos emergence as well as their anatomical alterations, were evaluated within 24 to 35 days PI; recreating the pupal development and their hatching in the soil under controlled laboratory conditions. CL50 and CL90 for the larvae phase were estimated through Probit regression analysis. Results: M. citrofolia concentrations of 400 and 460 mg/mL had a significant (p<0.05) larvicidal effect of 40% (95% CI 34.7 - 43.9) and 60% (95% CI 56.8 - 67.3), respectively. The pupicidal effect on the surviving larvae was significant (p<0.05) at 300, 400, and 460 mg/mL: 40% (95% CI 37.9 - 42.3), 60% (95% CI 55.7 - 65.9) and 70% (CI 95% 67.1 – 76.7), respectively. The inhibition of the emergence of imagos was significant (p<0.05) 50% (95% CI 42.3 - 57.8) in all concentrations equal to or greater than 200 mg/mL. Finally, 20% (95% CI 12.6 - 29.3) of the emerging imagos at 460 mg/mL presented morphoananomic alterations (p<0.05). The LC50 and LC90 estimated (larval phase) were 22.36 mg/mL (95%CI 15.06-33.19) and 245.08 mg/mL (95%CI 165.10-363.82), respectively. Conclusions: The methanolic extract of M. citrifolia was effective as larvicide, altering the pupation and the emergence of imagos of D. hominis. In addition, it modified the imagos morphoanatomy; interesting results to promote in-situ and other bioguided fractionation studies of this extract in different D. hominis stages; being M. citrifolia a plant species widely adapted to the conditions of the Meta department, Colombia.